Disentangling determinants of insecticide use to manage production, food security, and health risks in Cambodia and Vietnam: evidence from household surveys and risk-assessment experiments - Zhang, Wei; Liu, Yanyan; Bell, Andrew R. (Elsevier, 2019)
Insect pest problems are among the main causes of crop yield losses in global agriculture. Insecticides protect households from food-security and income shocks, but can induce human health and environmental risks. Semi-subsistence farm households (SSFHs), which farm for both consumption and market, make decisions about crop management and output allocation to maximise food consumption, income, and health outcomes, depending on their risk preferences and other household and community characteristics. In this study, we aimed to disentangle the determinants of insecticide use by SSFHs and identify whether health consideration has had any effect on insecticide use.